Diagnosis beyond the screen: characterization of Instagram posts on Stomatology and Oral Pathology (Research, Society and Development, 2022)
Instagram has proven to be an important resource for complementing learning in various areas of knowledge, including Dentistry. The aim of this study was to characterize the content of Instagram pages about stomatology and oral pathology and identify the level of scientific evidence present in the posts. The last 5 posts of 110 public Instagram pages, focused on oral lesions or changes in normality located from the hashtags, #stomatology, #oral pathology, #oral pathology, #oral medicine, #oral pathology and #oral health were evaluated. A script developed by the researchers through Google Forms was used as a research instrument, which provided descriptive statistics. The GRADE and Oxford University guides were used to analyze the scientific evidence. It was shown that the scientific quality of publications focused on stomatology and oral pathology in this social network is precarious, since most (62.7%) do not present any reference that corroborates the statements made. As a result, 98.2% of the posts fall within level 5 (lowest) of the Oxford list and 100% of the publications fall within the very low level of the GRADE system. It is evident that the degree of reliability of the publications found by this research is low, which demands more training in the search for information through social networks. Further studies on this topic are necessary, given the widespread use of social networks by dental academics.